2009
DOI: 10.2514/1.39191
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model for Human-Unmanned Vehicle Systems

Abstract: Advances in automation are making it possible for a single operator to control multiple unmanned vehicles (UVs). However, the complex nature of these teams presents a difficult and exciting challenge for designers of human-UV systems. To build such systems effectively, models must be developed that describe the behavior of the human-UV team and that predict how alterations in team composition and system design will affect the system's overall performance. In this paper, we present a method for modeling human-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…RESCU was initially used to analyze how changes in team size, robot-autonomy characteristics, and the human-robot interface affect the HMRS's performance [19], [20]. In this paper, we are interested in how OAASs, or the way operators allocate their attention among multiple robots, affect HMRS's effectiveness.…”
Section: B Operator Attention Allocation In Rescumentioning
confidence: 99%
See 3 more Smart Citations
“…RESCU was initially used to analyze how changes in team size, robot-autonomy characteristics, and the human-robot interface affect the HMRS's performance [19], [20]. In this paper, we are interested in how OAASs, or the way operators allocate their attention among multiple robots, affect HMRS's effectiveness.…”
Section: B Operator Attention Allocation In Rescumentioning
confidence: 99%
“…Previous studies have demonstrated that a stochastic discreteevent simulation can provide reasonably good predictions of how changes in team size, robot autonomy, and human-robotinterface characteristics alter system effectiveness [19], [20], [24]. In this paper, we evaluate the ability of this same modeling method to estimate the effects of OAASs on system effectiveness in RESCU.…”
Section: Modeling the Effects Of Oaassmentioning
confidence: 99%
See 2 more Smart Citations
“…The human-centric method is to evaluate the system autonomy on the basis of human performance or human model. Crandall proposed analogous concepts to allocate operator ' s attention, in order to maximize team performance with the given appropriate threshold of human workload [4], [5]. The robot-centric method builds the system autonomy evaluation on the capa bility of autonomous vehicles under the situations.…”
Section: School Of Electromechanical and Information Engineeringmentioning
confidence: 99%